Legal Responses to Sexual Orientation Related Marital Breakdown: A Comparative Analysis of Islamic Family Law and Indonesian State Law - Danil, Rahmadanil; Yaswirman; Yasniwati; Devianty Fitri; Wan Minto, Deri (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
Marital breakdown due to sexual orientation is becoming an increasingly visible phenomenon in Indonesian courts, but it remains in a gray area in both Islamic family law and national law. This study aims to analyze how both legal systems respond to this issue, both through written norms and jurisprudential practice, while identifying points of convergence and divergence between the two. Using qualitative research methods with a normative comparative approach, this study examines classical and contemporary fiqh literature and legislation. The findings show that although fiqh and Indonesian positive law depart from different epistemological orientations fiqh is based on ethical-normative principles and state law is based on legal-formalist principles both have important intersections in the form of the principle of preventing harm, recognition of factual disharmony, and psycho-social protection of couples. but there are significant differences in the categories of disgrace, standards of evidence, and the scope of judicial discretion, which lead to disparities in rulings. This research contributes to the development of family law discourse by offering a harmonization framework based on maqāṣid al-sharī'ah and a harm-based reasoning approach, as well as recommending interpretive guidelines that can increase legal certainty and protection of couples' rights in marriage cases involving sexual orientation.